Urban solutions to climate change: an overview of the latest progress - Kuok Ho Daniel Tang (Academia Environmental Sciences and Sustainability)
Urban centers are bearing the brunt of climate change. Meanwhile, they are important sources of greenhouse gases. This worsens the urban impacts of climate change. Urban solutions have emerged as feasible approaches to mitigate or adapt to climate change. This review provides an overview of the latest progress in various urban solutions to climate change. Urban solutions can generally be categorized into nature-based, technological, social, and integrated solutions. Nature-based solutions use natural ecosystems and processes, such as urban greening, green space, ecosystem restoration, and sustainable drainage systems, to address climate change problems. They could be vulnerable to the very climate challenges they address. Technological solutions encompass sustainable heating and cooling, innovative and green building materials, retro-reflective materials, cleaner modes of transportation, and big data and IoT devices for city planning. These solutions could be costly and resource-intensive. Social solutions involve promoting changes in behaviors and habits, which may require government and community intervention and engagement. They rely on political representation and social integration, which are sometimes lacking. Urban solutions are often integrated, combining two or more categories of solutions. Nature-based and technological solutions have been supported through urban greening and transportation plans aiming to encourage behaviors such as community-led greening and using public transport. Techno-ecological approaches are evident in urban greening that embeds technology. Social elements are incorporated to garner inclusiveness and engagement. However, integration is inherently complex as it involves multiple stakeholders. Potential suggestions for better integration of urban solutions are community engagement, policymaking, government support, and awareness-raising.